The Structure of Repetition by Export and Investigative Problems in Diwan of Enthusiasm for Abu Tammam - Jhada, Suaad Aziz (Journal of Tikrit University for Humanities, 2024)
The research article entitled "The Structure of Repetition by Export and Investigative Problems in Diwan of Enthusiasm for Abu Tammam" examines the profound influence exerted by the exported lines and the investigative difficulty within the framework of Enthusiasm poetry. The poets selected by Abu Tammam were chosen based on the preferences of a proficient critic and the sensibilities of a refined poet. The research included the representations of their lines, focusing on the patterns of repetition in their creative creation. Specifically, the structure of repetition and the investigative difficulties posed by these poets were explored without incurring any costs. Undoubtedly, the influence of these two artistic forms significantly shapes the semantic and melodic aspects within the poetry setting. The researcher employed a descriptive analytical approach to select verses that reflected the prominent ideas and trends of enthusiastic poets. These ideas were then examined in relation to the artistic and musical construction of poetic texts. The study focused on the mechanism of repetition, which was mediated by investigative problems. The researcher also explored the export and balance between these ideas within the context of their occurrence in the texts. The analysis also considered the pattern of verbal repetition of words within the poetic house.